Study of the Geological Structure of the Jabrayil Foothills - Mammadova, S.B.; Jafarova, E.N. (Herald of Azerbaijan Engineering Academy, 2023)
The article is devoted to the study of the geological structure of the Jabrayil foothills. The Jabrayil foothill plain is located in the southern part of the Republic of Azerbaijan. Climatic conditions are very different in the area. The average annual temperature varies from 10° to 13° C. The amount of atmospheric sediments is unevenly distributed throughout the area. Most sediments occur in the form of rain. The soil cover in the study area is mountain chestnut. Mesacaine sediments are involved in the structure of the study area. The lithological area consists of river stones-gravel, clay and clays.